Emerging Research in Web Information Systems and Mining International Conference, WISM 2011, Taiyuan, China, September 23-25, 2011. Proceedings - Zhiguo, Gong.; Luo, Xiangfeng; Chen, Junjie; Wang, Fu Lee.; Lei, Jingsheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes, together with LNCS 6987 and LNCS 6988, the refereed proceedings of the International Conference on Web Information Systems and Mining, WISM 2011, held in Taiyuan, China, in September 2011. The 112 revised full papers presented in the three volumes were carefully reviewed and selected from 472 submissions. The 61 papers presented in this volume are organized in topical sections on applications of artificial intelligence; applications of computational intelligence; automated problem solving; brain models/cognitive science; data mining and knowledge discovering; expert and decision support systems; fuzzy logic and soft computing; intelligent agents and systems; intelligent control; intelligent image processing; intelligent scheduling; intelligent signal processing; natural language processing; nature computation; neural computation; pattern recognition; rough set theory.
Keywords: Computer science; Software engineering; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Computer Science; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Software Engineering; Data Mining and Knowledge Discovery; Multimedia Information Systems